The Correlation Between Students’ Interest In Speaking And Students Speaking Achievement At XITH Grade Of MAN 2 Bukittinggi - Fatima; Hilma Pami Putri (CV. Ulil Albab Corp, 2022)
This study aims to determine the relationship between student interest and students' speaking scores in class XI MAN 2 Bukittinggi in the 2020/2021 academic year. This study uses a quantitative approach to the type of correlation design. The population in this study were all class XI at MAN 2 Bukittinggi consisting of 10 classes with a sample consisting of 71 students taken through a purposive technique. Data collection is done through questionnaires and tests. Students were asked to fill out a questionnaire related to their interest in speaking. The speaking data was taken from tests conducted in class. Researchers used SPSS for 20 windows to manage the data. The researcher used the Person Product Moment formula to determine the direction of the correlation and the magnitude of the correlation between students' interest in speaking and student achievement. The results of this study indicate that there is a relationship between students' interest in speaking and the achievement of speaking skills in class XI MAN 2 Bukittinggi in the 2020/2021 school year. The researcher found that the correlation coefficient between students' interest in speaking and the achievement of speaking skills in class XI MAN 2 Bukittinggi is 0.508. The correlation was positive and significant. This means that Ho is rejected and Ha is accepted. Thus, there is a positive relationship between students' interest in speaking and the achievement of speaking skills in class XI MAN 2 Bukittinggi. Based on the results of the study, it can be concluded that the higher the student's interest in speaking, the better the achievement of speaking skills.